2019
DOI: 10.1177/1071100719837524
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Comparison of Low-Profile Contoured Locking Plate With Single Compression Screw to Fully Threaded Compression Screws for First MTP Fusion

Abstract: Background: Open metatarsophalangeal (MTP) arthrodesis using locked plates produces good clinical outcomes. However, arthroscopic fusion with new-generation fully threaded compression screws is emerging as an alternative. The purpose of this study was to compare low-profile contoured locked plates with fully threaded compression screws for first MTP fusion, in a biomechanical cadaveric model. Methods: The first rays of 8 matched pairs of fresh frozen cadaveric feet underwent dissection and dual-energy x-ray ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…This evolving and ever-expanding list of fixation constructs has provided surgeons with many options when selecting hardware for first MTP arthrodesis, each with its own unique benefits and limitations. Current options for fixation devices include screws in various configurations, Kirschner wires (K-wires), Steinmann pins, monofilament wires, biodegradable rods, both locking and non-locking plates, memory compression staples, and various combinations of these fixation devices [7,11,[18][19][20][21].…”
Section: Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…This evolving and ever-expanding list of fixation constructs has provided surgeons with many options when selecting hardware for first MTP arthrodesis, each with its own unique benefits and limitations. Current options for fixation devices include screws in various configurations, Kirschner wires (K-wires), Steinmann pins, monofilament wires, biodegradable rods, both locking and non-locking plates, memory compression staples, and various combinations of these fixation devices [7,11,[18][19][20][21].…”
Section: Reviewmentioning
confidence: 99%
“…Fixation with screws has since changed drastically, but screws are still common means of fixation in first MTP arthrodesis. Currently, screw fixation is primarily in the form of a supplementary lag screw [11,16,20] or as the fixation construct itself, most commonly as a single screw, two parallel screws, or two crossed screws (Figure 1) [7,16,[22][23][24]. Studies have shown these methods of fixation to be acceptable options as they work well in patients with good bone quality and cause less postoperative irritation and discomfort due to their relatively low profile.…”
Section: Screwsmentioning
confidence: 99%
See 3 more Smart Citations